Muscle activity during fin swimming - Koch, M.; Gouvernet, G.; Chavet, P.; Barla, C.; Sabo, A. (Procedia Engineering, 2010)
Swimming fins are used for muscular training but we do not really know how fins affect muscular training. In this way, the purpose of this present study was to examine the influencing factors of fin designs and swimmer kinematics on the muscle activity. Eight individuals took part in this study which consists of eight tests, thereof one standard, four with prototyped fins and three with different kinematics. The surface electromyography (EMG) of lower limb superficial muscles was recorded. The muscle activity was significantly higher for highest frequency strokes. No EMG difference was found whilst comparing different amplitudes or different stiffness. Heavy fins significantly train the shank more, whereas short ones have more impact on the thigh and the buttocks.